Analisis Penilaian Persediaan Beras Terhadap Perolehan Laba Pada PT. Indogrosir Samarinda - Nikke Yudha Karyaning Pratiwi; Elfreda Aplonia Lau; Heriyanto - (Common Publisher, 2020)
This research is aimed to determine the rice inventory assessment towards greater earnings with research problem whether the assessment of rice inventories using First In First Out (FIFO) method gains in greater profit compared to using Last In First Out (LIFO) method and Average method? The basic theory in this research is inventory management using First In First Out (FIFO) method, Last In First Out (LIFO) method, Average method and financial statements. While the tools of analysis used are First In First Out (FIFO) method, Last In First Out (LIFO) method, Average method and company’s profit calculation. The results of the research, it is concluded that First In First Out (FIFO) method would provide a lower cost of goods sold compared to Last In First Out (LIFO) method and Average method, so that the profit would be greater if compared to Last In First Out method ( LIFO) as well as Average method.